Green finance in Europe: Strategy, regulation and instruments - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
The "European Green Deal" stipulates that the EU will become climate-neutral by 2050. This transformation requires enormous investments in all major sectors including energy, mobility, industrial manufacturing, real estate and farming. Although the EU Commission has announced that a total of EUR 1 trillion will be invested into the green transformation of the European economy over the next ten years, the majority of the investments must be financed by the private sector. Alongside many factors affecting a successful implementation of the Green Deal, a regulatory framework for the financial industry has to be established to facilitate the financing of sustainable investments. To that end, the European Sustainable Finance Strategy lays the foundation for a complex set of different measures that have been launched in recent years. This article provides a comprehensive overview of key regulatory initiatives such as the taxonomy regulation, the disclosure frameworks for both corporates and financial institutions and other aspects of financial market regulation that have already significantly improved the regulatory framework for sustainable finance. Nevertheless, some additional instruments could be considered, such as a reform of top management remuneration or the provision of tax incentives for green investments in the real economy, and these are briefly discussed.
Keywords: G10; G20; 330; Klimapolitik; EU-Umweltpolitik; Green Deal; EU-Staaten